Beyond motivation: Creating supportive healthcare environments for engaging in therapeutic patient education according to healthcare providers - Bob C. Mulder; Hylkje Algra; Esther Cruijsen; J. Marianne Geleijnse; Renate M. Winkels; Willemieke Kroeze (PEC Innovation)
Objective: This article reports the findings of focus-group discussions with healthcare providers concerning the facilitators and barriers they experience when engaging in therapeutic patient education (TPE). Methods: Five focus-group discussions were held with a total of 21 primary and secondary healthcare providers. Discussions were moderated using a topic list that was co-created with healthcare providers. All discussions were recorded, transcribed verbatim and analysed thematically. Results: Healthcare providers consider TPE important, but it requires long-term, continuous effort in order to be effective. They sometimes doubt its effectiveness and their own efficacy. Moreover, healthcare providers experience a lack of a supportive environment. Overall, their experiences could be captured in four categories of determinants of engaging in TPE: Capabilities, Motivation, Physical Context and Social Context. Conclusion: Therapeutic patient education requires healthcare providers to be capable and motivated. To maintain the continuous effort needed, healthcare providers need to be supported both socially (e.g. by colleagues and management) and physically (e.g. through communication infrastructure). Innovation: In contrast to previous studies focusing on the motivation and capability of healthcare providers to perform TPE, this study contributes to innovation in health communication by identifying social and physical factors that determine whether TPE is delivered continuously under actual or perceived constraints in terms of time and effectiveness.